Is reflective practice an essential component of becoming a professional teacher?. Issue 3 (3rd May 2016) - Meierdirk, Charlotte
Abstract: This paper explores the concept of reflective practice and its role in the professionalisation of student teachers. There is an examination of the requirements to become a qualified teacher and how these requirements have determined practice. After looking at the recent evolution of state requirements for initial teacher education, in England, it investigates the place of reflective practice within that process and to what extent reflective practice is still needed to become a teacher. It presents the different interpretations of reflective practice and the role of professionalism in the journey to qualified teaching status (QTS).